2006
DOI: 10.1007/s11060-005-9092-y
|View full text |Cite
|
Sign up to set email alerts
|

Chordoid Meningioma, an uncommon variant of meningioma: A clinicopathologic study of 12 cases

Abstract: Chordoid meningiomas are predominantly tumors of young adults with predilection for supratentorial location. Intraventricular location, absence of systemic manifestations despite the presence of abundant B-lymphocytes, presence of mast cells and low MIB-1 LI are some of the interesting findings in the present series, which need documentation. Hence, larger number of cases with adequate follow-up data need to be studied further to establish the clinical significance of this variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 24 publications
6
76
3
1
Order By: Relevance
“…A little more than 100 cases of chordoid meningioma have been described in the English-language literature, the majority of which are in the pathology and neurosurgery literature. [4][5][6][7][8][9] Attempts to distinguish benign from atypical and malignant meningiomas have been undertaken with variable results, and DWI and ADC values have provided the most reliable means of differentiation, 10,11 though no data analysis specifically examining the chordoid morphologic variant has been performed. To the best of our knowledge, only 3 case reports in which the MR imaging characteristics of chordoid meningiomas were described have been published in the radiology literature.…”
Section: Resultsmentioning
confidence: 99%
“…A little more than 100 cases of chordoid meningioma have been described in the English-language literature, the majority of which are in the pathology and neurosurgery literature. [4][5][6][7][8][9] Attempts to distinguish benign from atypical and malignant meningiomas have been undertaken with variable results, and DWI and ADC values have provided the most reliable means of differentiation, 10,11 though no data analysis specifically examining the chordoid morphologic variant has been performed. To the best of our knowledge, only 3 case reports in which the MR imaging characteristics of chordoid meningiomas were described have been published in the radiology literature.…”
Section: Resultsmentioning
confidence: 99%
“…In our study we found an association between the presence of mast cells and brain oedema, especially in high grade group, however, there was no statistically significant correlation between both parameters because of low number of examined cases. Epari et al [12] and Tena-Suck et al [13] observed a significant number of mast cells and B lymphocytes in chordoid meningioma, in the stroma of connective tissue. Similar to our results were obtained by Bo et al [14] who observed a statistically significant association between the number of macrophages and mast cells and microscopic features of aggressiveness, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…In the event of subtotally resected intracranial CMs, post-operative radiotherapy is the standard treatment (10,14). Due to the aggressive growth pattern of spinal CMs and long-term fatal outcome in the present patient, post-operative early adjuvant radiotherapy and close follow-up investigation in adult and pediatric patients is recommended, although certain studies debate the benefit of post-operative adjuvant treatments in pediatric patients (2,7,15).…”
Section: Discussionmentioning
confidence: 99%